Alcohol industry involvement in the delayed South Africa Draft Liquor Amendment Bill 2016: a case study based on freedom of information requests - Gemma Mitchell; Pfumelani Siwela; Susan Goldstein; Aadielah Maker Diedericks (Globalization and Health)
Abstract Background South Africa is reported to have one of the highest per capita rates of alcohol consumption among drinkers globally, with alcohol harms exacerbating socio-economic inequalities in the country. The Draft Liquor Amendment Bill 2016 proposed new restrictions on alcohol advertising, availability, and liability of retailers and manufacturers for harm related to any contravention of the regulations. To date, the Bill has not progressed through the legislative process. The alcohol industry is known to use a diverse set of strategies to delay evidence-based policies globally. Methods We aimed to explore Bill-related activity by industry within the National Economic and Development Labour Council, a multi-stakeholder forum that assesses socio-economic policies before they reach parliament. On 06 July 2023 we made a Request for Access to Record, using form two of the Promotion of Access to Information Act (PAIA), no. 2 of 2000 to the National Economic and Development Labour Council for access to minutes of all meetings, reports, and any other publications related to the Bill between January 2016 and December 2022. Informed by Ulucanlar et al’s (2023) model and taxonomies of corporate political activity, we extracted data on industry Bill-related activity and thematically analysed key events, presented here as a narrative synthesis. Results We identified activity by 14 alcohol industry organisations related to the Bill between 2016 and 2022. Industry representation on five National Economic and Development Labour Council-related committees identified between 2017 and 2021 facilitated their involvement in Bill-related discussions and supported access to other government departments. Community representation was low in all committees compared to industry, labour, and government. Industry funded two socio-economic assessments of the Bill in 2017 and 2022, despite an independent socio-economic impact assessment having already been completed. The 2017 report delayed progress of the Bill, and the 2022 ‘re-evaluation’ was more critical of the proposed measures, with the differing conclusions attributed to different methodologies. During the covid-19 pandemic, industry used a ‘carrot and stick’ approach of legal threats and donations to attempt to move towards self-regulation via a social compact. The National Economic and Development Labour Council confirmed in 2023 that the social compact was unsuccessful. Conclusions Early ‘regulatory capture’ gave the alcohol industry the opportunity to shape assessment of the Bill within the National Economic and Development Labour Council. Our findings are in line with previous studies on corporate influence on policy globally, and support calls for a reassessment of the role and proportion of industry representation within the National Economic and Development Labour Council locally.